Industrial Ecological Parks: A Study on the Possibility of Applying the Kalundborg Park Experience in the Industrial City of Hassia (Journal of Hama University, 2026)
Industrial ecological parks are considered one of the pioneering models in achieving environmental and economic sustainability. They contribute to enhancing the efficiency of natural resource use, reducing waste, and lowering harmful emissions, making them a vital tool in addressing global environmental challenges such as climate change and resource depletion. Their significance lies in their ability to connect various industries within a collaborative network that yields mutual benefits, as demonstrated by successful examples like Kalundborg in Denmark. This study aimed to analyze the feasibility of applying the "industrial ecological parks" model, inspired by the Kalundborg experience, in the Hassia Industrial City in Syria, with the goal of exploring opportunities to improve environmental and economic performance in this context. The methodology relied on analyzing secondary data derived from previous studies and international reports, with a focus on the Kalundborg case study as a reference model. The results revealed the potential for significant reductions in carbon emissions by 50,000 tons annually and savings of approximately one million cubic meters of water, thereby enhancing water sustainability. However, the study highlighted key challenges, including the need for an initial investment estimated at 15 million USD and a lack of local technical expertise necessary for successful implementation. Accordingly, the study recommends establishing an effective resource-sharing network among industries and strengthening public-private partnerships to overcome implementation obstacles and ensure the project’s sustainability.